2023
DOI: 10.24875/gmm.m18000079
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and other factors associated to gonarthrosis

Abstract: Objective: To evaluate whether an association exists between gonarthrosis and metabolic syndrome X (MS) as well as other potential risk factors. Method: Comparative cross-sectional study of 310 patients evaluated by pathology of knee grouped in patients with gonarthrosis and without it. Sociodemographic, anthropometric and laboratory data was obtained. Gonarthrosis was defined as a ≥ score in Kellgren-Lawrence radiological scale, and MS was assessed using the International Diabetes Federation criteria. Odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Health Study, obese women with two or more cardiovascular disease risk factors reported knee pain in the past three years. 12 In the Japanese ROAD study, the risk of osteoarthritis increased with the presence of each component of the metabolic syndrome. 13 In addition, in a study in Russia with the presence of 1,350 people with osteoarthritis, 56.62% had metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health Study, obese women with two or more cardiovascular disease risk factors reported knee pain in the past three years. 12 In the Japanese ROAD study, the risk of osteoarthritis increased with the presence of each component of the metabolic syndrome. 13 In addition, in a study in Russia with the presence of 1,350 people with osteoarthritis, 56.62% had metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…14 Also, other studies have discussed the relationship between the components of metabolic syndrome and osteoarthritis. 12,13,15 Arthritis and obesity have been known to be related to each other in many studies. [14][15][16] Although the exact association mechanism between obesity and arthritis is unknown, studies report metabolic mechanical factors in this relationship.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation